2021
DOI: 10.1016/j.jagp.2021.05.026
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Suicidal Ideation in Older Adults: Two Case Reports With a Review of the Literature

Abstract: The COVID-19 pandemic may profoundly harm the mental health and emotional well- being of many older adults. Public health interventions to minimize the spread of the virus have had the unintended consequences of worsening social isolation, financial stress, and unemployment. Results of early research efforts assessing the impact of these interventions on the mental health of older adults have been mixed. Available findings suggest that a subset of community-dwelling older adults have been less negatively impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
10
0
1
Order By: Relevance
“…A longitudinal study across the pandemic waves in UK reported an increased rate of suicidal thoughts, especially among young female adults and those with preexisting mental health problems [ 28 ]. There have also been case reports of COVID-related suicides among older adults with a history of preexisting mental illnesses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study across the pandemic waves in UK reported an increased rate of suicidal thoughts, especially among young female adults and those with preexisting mental health problems [ 28 ]. There have also been case reports of COVID-related suicides among older adults with a history of preexisting mental illnesses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These 29 articles are included in this scoping review. Studies and other publications were quantitative studies ( n = 11; Azevedo et al, 2021; Barguilla et al, 2020; Chamberlain et al, 2020; Degen et al, 2021; El Haj et al, 2020; 2021; Pereiro et al, 2021; Tam et al, 2021; van Maurik et al, 2020; Xiang et al, 2021; Yu et al, 2021), qualitative studies ( n = 5; Alsawy et al, 2020; Biggs et al, 2019; Kontos et al, 2021; Steele et al, 2020; Talbot & Briggs, 2021), reviews ( n = 6; Iodice et al, 2021; Kimura et al, 2020; Morina et al, 2021; Ryoo et al, 2020; Simonetti et al, 2020; Soytas, et al, 2021), editorials or commentaries ( n = 4; Canevelli et al, 2020; Edelman et al, 2020; Hampel & Vergallo, 2020; Soares et al, 2020), and case studies ( n = 3; Asthana et al, 2021; Le Vasseur, 2021; Shea et al, 2020) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, research shows that, at young ages, such changes induced by stress in the structure and function of the prefrontal cortex (PFC) may not be permanent, but aging is associated with a decline in neuronal plasticity and resilience to the potentially detrimental impact of stress-induced changes in the PFC such as a decrease and shrinkage in synaptic density through a loss in dendritic spines (33,34). This evidence suggests that the neurobiological changes induced by stress are more inclined to have a long-lasting impact on older patients (31).…”
Section: Physical Function Problems (Impairments) Biological Factorsmentioning
confidence: 99%